2017
DOI: 10.18203/2320-6012.ijrms20175536
|View full text |Cite
|
Sign up to set email alerts
|

A study of effect of alcohol on liver function tests (LFT) in Garhwal hills, India

Abstract: Background: There has been frequent researches on liver pathologies and its variables in the world. There is no known research carried on liver in Garhwal region. Uttarakhand is one area where the hill people are more habitual of alcohol abuse and alcoholism is more endemic here. Primary objective was to correlate alcohol intake and its effect on liver function test. Secondary objectives were to screen the patients for abnormal LFTs and to observe and understand changes needed in lifestyle to reduce risk of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…The AST and ALT were all significantly increased in all participant groups when compared to control (non-alcohol consumers). These findings were in agreement with various authors who suggested the increased activity of these enzymes to the unique role of a hepatic cell as the primary site of alcohol metabolism [12][13][14] . Most of the current studies were still in agreement with studies indicating that aspartate and alanine aminotransferase (AST and ALT) as biomarkers for disorders associated with heavy alcohol drinkers [15][16][17][18][19] .…”
Section: Discussionsupporting
confidence: 93%
“…The AST and ALT were all significantly increased in all participant groups when compared to control (non-alcohol consumers). These findings were in agreement with various authors who suggested the increased activity of these enzymes to the unique role of a hepatic cell as the primary site of alcohol metabolism [12][13][14] . Most of the current studies were still in agreement with studies indicating that aspartate and alanine aminotransferase (AST and ALT) as biomarkers for disorders associated with heavy alcohol drinkers [15][16][17][18][19] .…”
Section: Discussionsupporting
confidence: 93%